Dual Functional Conjugated Acetylenic Polymers: High-Efficacy Modulation for Organic Photoelectrochemical Transistors and Structural Evolution for Bioelectronic Detection - Chen, Jia-Hao; Wang, Cheng-Shuang; Li, Zheng; Hu, Jin; Yu, Si-Yuan; Xu, Yi-Tong; Lin, Peng; Zhao, Wei-Wei (Analytical chemistry (Washington), 2023)
Conjugated acetylenic polymers (CAPs) have emerged as a unique class of metal-free semiconductors with tunable electrical and optical properties yet their full potential remains largely unexplored. Organic bioelectronics is envisioned to create more opportunities for innovative biomedical applications. Herein, we report a poly(1,4-diethynylbenzene) (pDEB)/NiO gated enhancement-mode poly(ethylene dioxythiophene)–poly(styrene sulfonate) organic photoelectrochemical transistor (OPECT) and its structural evolution toward bioelectronic detection. pDEB was synthesized via copper-mediated Glaser polycondensation of DEB monomers on the NiO/FTO substrate, and the as-synthesized pDEB/NiO/FTO can efficiently modulate the enhancement-mode device with a high current gain. Linking with a sandwich immunoassay, the labeled alkaline phosphatase can catalyze sodium thiophosphate to generate H2S, which will react with the diacetylene group in pDEB through the Michael addition reaction, resulting in an altered molecular structure and thus the transistor response. Exemplified by HIgG as the model target, the developed biosensor achieves highly sensitive detection with a linear range of 70 fg mL–1–10 ng mL–1 and a low detection limit of 28.5 fg mL–1. This work features the dual functional CAP-gated OPECT, providing not only a novel gating module but also a structurally new rationale for bioelectronic detection.